Measuring static seated pressure distributions and risk for skin pressure ulceration in ice sledge hockey players. (2nd April 2016) - Darrah, Shaun D.; Dicianno, Brad E.; Berthold, Justin; McCoy, Andrew; Haas, Matthew; Cooper, Rory A.
Abstract: Purpose : To determine whether sledge hockey players with physical disability have higher average seated pressures compared to non-disabled controls. Method : Fifteen age-matched controls without physical disability and 15 experimental participants with physical disability were studied using a pressure mapping device to determine risk for skin pressure ulceration and the impact of cushioning and knee angle positioning on seated pressure distributions. Results : Regardless of participant group, cushioning, or knee angle, average seated pressures exceeded clinically acceptable seated pressures. Controls had significantly higher average seated pressures than the disability group when knees were flexed, both with the cushion ( p = 0.013) and without ( p = 0.015). Knee extension showed significantly lower average pressures in controls, both with the cushion ( p < 0.001) and without ( p < 0.001). Placement of the cushion resulted in significantly lower average pressure in controls when knees were extended ( p = 0.024) but not when flexed ( p = 0.248). Placement of the cushion resulted in no difference in pressure ( p = 0.443) in the disability group. Conclusions : Pressures recorded indicate high risk for skin ulceration. Cushioning was effective only in the control group with knees extended. That knee extension significantly lowered average seated pressures is important, as many sledge hockey players utilize positioning with larger knee flexion angles. Implications for Rehabilitation: Ice sledge hockey is a fast growing adaptive sport. Adaptive sports have been associated with several positive improvements in overall health and quality of life, though may be putting players at risk for skin ulceration. Measured static seated pressure in sledges greatly exceeds current clinically accepted clinical guidelines. With modern improvements in wheelchair pressure relief/cushioning there are potential methods for improvement of elevated seated pressure in ice hockey sledges.